Another new karst-dwelling rock gecko in the Cnemaspis siamensis group (Reptilia, Gekkonidae) from Kanchanaburi Province, western Thailand - Attapol Rujirawan; Akrachai Aksornneam; Siriporn Yodthong; Parinya Pawangkhanant; Bryan L. Stuart; Anchalee Aowphol (ZooKeys)
A new species of the Cnemaspis siamensis group is described from Wang Khrachae District, Kanchanaburi Province, western Thailand based on morphological and molecular data. The new species, Cnemaspis enneaporus Rujirawan, Aksornneam & Aowphol, sp. nov., is distinguished from other species in the C. siamensis group by having the combination of SVL 42.2 mm in adult male (n = 1), 43.7 mm in adult female (n = 1); eight supralabials; seven or eight infralabials; ventral scales smooth; nine continuous precloacal pores in male; 17 or 18 paravertebral tubercles linearly arranged; tubercles on lower flanks present; lateral caudal furrows present; no caudal tubercles in the lateral furrows; ventrolateral caudal tubercles present on original portion of tail; caudal tubercles not encircling tail; subcaudals smooth; no enlarged median subcaudal row; two postcloacal tubercles on each side of tail; no shield-like subtibial scales; subtibial scales smooth; no enlarged submetatarsal scales; 26–28 subdigital lamellae on the fourth toe; sexually dimorphic for dorsal and ventral colour pattern; prescapular marking absent; gular marking absent; and yellow colouration in life on all ventral surfaces of head, body and tail in adult male. Phylogenetically, the new species is recovered as the sister taxon to C. huaseesom, but the two species are separated by 8.3–9.4% uncorrected pairwise genetic divergences in the mitochondrial NADH dehydrogenase subunit 2 gene and flanking tRNAs.